The Role of the Holy Spirit in Pentecostal Worship in the Light of John 4:20-26 and Ephesians 5:18-20 - Lee Roy Martin (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
The importance of worship for the Pentecostal church can hardly be overstated, and the worship practices of the global church have been altered significantly by the influence of the Pentecostal movement. This article will address the biblical and theological foundations of Spirit-filled worship, focusing particularly on the role of the Holy Spirit in worship, through a literary-theological interpretation of two key biblical texts—John 4:20-26 and Ephesians 5:18-20. The study finds that from the viewpoint of these texts, the Holy Spirit is an indispensable element in Christian worship and is deeply active in the practices of worship.